Protocols for treating patients with end‐stage renal disease: a survey of AEGD/GPR dental residencies. (5th August 2016) - Howell, Scott; Perry, Maureen Munnelly; Patel, Nipa
ABSTRACT: Rationale/Background: Approximately 14% of Americans are living with chronic kidney disease (CKD). The prevalence of end stage renal disease (ESRD), the result of progressing CKD continues to rise by 21, 000 per year.Currently the only antibiotic prophylaxis guidelines for patients with end‐stage renal disease undergoing dental treatment were published by the AHA in 2003. Presented in three parts, the first part of this study found no consistent protocols amongst U.S. dental schools. The goal of the second part of the project was to determine the current protocol being used to treat ESRD patients at accredited U.S. AEGD and GPR programs. Methods and Materials: A 20 multiple choice question survey was e‐mailed to 262 directors of AEGDs and GPRs within the United States regarding renal treatment protocol details and antibiotic prophylaxis for patients with renal disease. Results: 34% of respondents reported having an established renal treatment protocol. For programs with a protocol, 65.5% of programs reported following AHA guidelines. Conclusion: There is a lack of consistent, established protocols amongst U.S. AEGD and GPR programs. It is suggested that updated and evidence based guidelines for the safe treatment of patients be developed.